2008
DOI: 10.1248/bpb.31.775
|View full text |Cite
|
Sign up to set email alerts
|

Cold-Induced Changes in Gene Expression in Brown Adipose Tissue: Implications for the Activation of Thermogenesis

Abstract: Brown adipose tissue (BAT) is the site of heat production (thermogenesis). This unique function is performed by uncoupling protein 1 (UCP1) specifically expressed in mitochondria of BAT. UCP1 dissipates the driving force of ATP synthesis, and thus causes heat production followed by energy expenditure. The thermogenic function of BAT has the role of maintaining body temperature under cold conditions. When animals are exposed to cold, the expression of UCP1 gene is increased to activate thermogenesis. To date, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 124 publications
(155 reference statements)
2
23
0
1
Order By: Relevance
“…Previous studies have shown that gene expression of Fabp3 in the BAT of non-breeding rats is induced by cold exposure and reduced at high ambient temperatures, closely resembling the expression profile of UCP1 (Watanabe et al, 2008;Yamashita et al, 2008). These changes in Fabp3 expression were confirmed at the protein level, indicating an essential role of Fabp3 in fatty acid transport and its oxidation through the activity of UCP1 in cold-induced thermogenesis (Yamashita et al, 2008).…”
Section: Fabp3 Gene Expression: An Unexpected Resultsmentioning
confidence: 58%
“…Previous studies have shown that gene expression of Fabp3 in the BAT of non-breeding rats is induced by cold exposure and reduced at high ambient temperatures, closely resembling the expression profile of UCP1 (Watanabe et al, 2008;Yamashita et al, 2008). These changes in Fabp3 expression were confirmed at the protein level, indicating an essential role of Fabp3 in fatty acid transport and its oxidation through the activity of UCP1 in cold-induced thermogenesis (Yamashita et al, 2008).…”
Section: Fabp3 Gene Expression: An Unexpected Resultsmentioning
confidence: 58%
“…Alternatively, it may also be possible that valine deprivation has a direct effect on thermotaxic center. Thus, one of the adaptive changes occurs at this case is to increase UCP1 expression in BAT, thereby to maintain normal body temperature, as many studies reported for the function of UCP1 (Watanabe et al 2008;Enerback et al 1997). Both possibilities, however, will be investigated in the future.…”
Section: Discussionmentioning
confidence: 90%
“…Therefore, it would be expected that after a longer period of cold exposure, optimal adaptation to this environment would be achieved, and thus, an increase in food intake would be observed. Cold stimulus increases sympathetic activity, and the catecholamines released from sympathetic innervations, acting mainly through β3 adrenergic receptors, stimulate lipolysis (and fatty acid release) in WAT and BAT and thermogenesis in BAT [35,36]. Detailed in vivo and in vitro studies have suggested an important role of ATGL in lipid mobilization in response to cold stimuli and isoproterenol treatment [10,12].…”
Section: Discussionmentioning
confidence: 99%